Penerapan Metode VIKOR untuk Penentuan Tempat Melukat di Kabupaten Buleleng - Gede Surya Mahendra; Kadek Dwika Darma Widyaputra (Jurnal IT UHB, 2026)
Buleleng Regency has several melukat (purification) sites that are significant for Hindus and also attract interest as religious tourism destinations. Currently, determining the best melukat site is performed manually. Therefore, a decision support system (DSS) is needed to provide optimal recommendations. This study uses the VIKOR method because of its capability to solve multi-criteria problems quickly and accurately. The alternatives analyzed consist of seven (7) melukat sites in Buleleng Regency, namely Pura Tirta Sudhamala, Pura Taman Sari, Pura Goa Raja Tajun, Pura Sakti, Pura Ponjok Batu, Pura Pesiraman, and Pura Tirta Masem. The criteria used include facilities, road accessibility, natural beauty, parking availability, entrance ticket costs, and distance from the city center. The results showed that the recommended melukat site is Pura Taman Sari with a value of 0, followed by Pura Ponjok Batu in the second position with a value of 0.0309. Pura Tirta Sudhamala occupies the third position with a value of 0.4668, followed by Pura Sakti in the fourth position with a value of 0.5206. Pura Pesiraman is in the fifth position with a value of 0.8138. Meanwhile, Pura Tirta Masem occupies the sixth position with a value of 0.9104, and Pura Goa Raja Tajun is in the last position with a value of 1.